Confirmation of the presence of Ischnura senegalensis (Rambur, 1842) on the Canary Islands - Sánchez–Guillén R. A.; Cordero–Rivera, A. (Animal Biodiversity and Conservation, 2015)
The presence of one or two species of damselflies of the genus Ischnura in the Canary Islands has been a matter of debate in the recent years. The first published records listed I. senegalensis as the only zygopteran inhabiting the archipelago, but this proved to be wrong, and until recently, all specimens of Ischnura captured in the islands were unanimously regarded as belonging to I. saharensis. Recent photographic evidence, however, is compatible with the presence of I. senegalensis. In this study, we give morphological and genetic evidence of the presence of I. senegalensis in the Canary Islands, and we discuss the importance of voucher specimens to correctly identify very similar species.